Aplicación del lecitina de soya y relación aceite-agua en la estabilidad de la margarina de maní (Arachis hypogaea L) - Verduga Solórzano, Rubén Darío (2014)
This research was conducted in order to determine the stability and acceptability of peanut margarine, made from two bases components-water peanut oil and soy lecithin as an emulsifier and stabilizer. Design was used in two-factor completely randomized arrangement AxB with three replicas. Factor A: study factors ratio manipulated oil-water (75% / 12%, 85% / 10%, 80% / 16%) and B: Percentage of soybean lecithin (5%, 8%, 11% ) consistency was assessed by consistometer Adams, iodine (NTE INEN 0161) saponification (NTE INEN 0161), Refractive Index (NTE INEN 0161), physicochemical parameters such as moisture, acidity, sodium chloride (NTE INEN 276), and by technical panel sensory (texture, flavor) .The treatments were analyzed by ANOVA at 5% significance level was used as the experimental unit 250g. It was determined A3B3 (96% fat / water) + 11% lecithin), as the best treatment according to the results of the analysis showed a high iodine value and refractive establishment of more; the results were: I. Iodine = 107.53 cg / g, I. Saponification = 190,75mg / g, I. Refraction = 1.4560. As for the physical-chemical analyzes were: moisture = 1.56% Acidity = 2.19%, sodium chloride = 0.05%; this treatment was evaluate by a technical panel showing good sensory acceptability according to their taste and texture.